On the asymptotic normality of the estimate of the spectral function - Bentkus, R. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Бенткус. Об асимптотической нормальности оценки спектральной функцииR. Bentkus. Apie spektrinės funkcijos įvertinimo asimptotinį normalumą